Andorra - Cameron, Peter (Farrar, Straus, Giroux, 1997)
A man's unsuccessful attempt to flee his past. For his new life Alexander Fox, who is an American, chooses Andorra, a quiet spot sandwiched between France and Spain. But loneliness leads him into new relationships--he becomes a suspect in a murder--and has to flee once more.
Keywords: Alltag, Brauchtum; Andorra -- Fiction; Andorra -- Social life and customs -- Fiction; Love stories